Real-time satellite data for natural resources management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
John Stephenson and Jim Williams explain how weather satellite data reception systems are making remote sensing data more accessible for a variety of local applications.